Translating a Tourism Booklet Entitled “Booklet Wisata Kabupaten Jember” - Siti Nur Rohmah; Gullit Tornado Taufan (Journal of Language, Communication, and Tourism, 2023)
Considering the tourism potentials in Jember, the efforts in promoting the tourism in the area should be done by utilizing any promotional media including tourism booklet. The local government of Jember had published a printed promotional media entitled “Booklet Wisata Kabupaten Jember”. The booklet was written in Indonesian. Therefore, it was essential to translate the booklet into English to attract more visitors to come to Jember especially foreign tourists. In translating the booklet, there were four stages employed including analysis, transfer, restructure, and evaluation and revision. The key and essential parts of current translation were the analysis and evaluation and revision. The writers needed to analyze the source text carefully do to textual and substantial issues. In addition, evaluation and revision were also done by considering the perspective of the target readers. The final product of the translation was an English version of the booklet with the title of “Jember Tourism Booklet: Explore the Beauty of Jember”.